2011
DOI: 10.1016/j.jenvman.2011.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Identifying priority areas for ecosystem service management in South African grasslands

Abstract: a b s t r a c tGrasslands provide many ecosystem services required to support human well-being and are home to a diverse fauna and flora. Degradation of grasslands due to agriculture and other forms of land use threaten biodiversity and ecosystem services. Various efforts are underway around the world to stem these declines. The Grassland Programme in South Africa is one such initiative and is aimed at safeguarding both biodiversity and ecosystem services. As part of this developing programme, we identified sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
96
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(101 citation statements)
references
References 31 publications
1
96
1
3
Order By: Relevance
“…Despite the limitations of our study, some implications can be drawn for policies in Costa Rica. The positive correlations between carbon, biodiversity and local services makes it possible to develop conservation policies with synergies for multiple ES, as in other countries (Chan et al 2006;Turner et al 2007;Bai et al 2011;Egoh et al 2011;Luck et al 2012). According to our results, current conservation policy mechanisms in Costa Rica contribute to the delivery of multiple ES: protected areas provide high levels of carbon and water-related services, and PES areas provide high levels of biodiversity, carbon and scenic beauty.…”
Section: Policy Implicationsmentioning
confidence: 53%
See 1 more Smart Citation
“…Despite the limitations of our study, some implications can be drawn for policies in Costa Rica. The positive correlations between carbon, biodiversity and local services makes it possible to develop conservation policies with synergies for multiple ES, as in other countries (Chan et al 2006;Turner et al 2007;Bai et al 2011;Egoh et al 2011;Luck et al 2012). According to our results, current conservation policy mechanisms in Costa Rica contribute to the delivery of multiple ES: protected areas provide high levels of carbon and water-related services, and PES areas provide high levels of biodiversity, carbon and scenic beauty.…”
Section: Policy Implicationsmentioning
confidence: 53%
“…For example, studies showed that habitats under conservation (for example in protected areas) provide more regulating and cultural ES than other habitats in Europe (Eigenbrod et al 2009;Maes et al 2012b). Most of these studies focus on the effects of biodiversity conservation policies, such as protected areas or agrienvironmental schemes, on other ES (Chan et al 2006;Egoh et al 2009Egoh et al , 2011. With the prospect of large global investments in reducing emissions from deforestation and forest degradation (REDD), some studies have analysed how carbon policies could benefit biodiversity (Strassburg et al 2010;Busch et al 2011). Mapping ES is at the heart of spatial analyses of ES relations (Eigenbrod et al 2010;Maes et al 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly pertinent to Cape Town, where the natural environment has a high biodiversity irreplaceability value and as a result the city presents a low choice environment where spatial planning decisions must be made under constrained circumstances. The option of matching ecosystem services and conservation targets, used for example by Egoh et al (2011), cannot be exercised. In this minimal choice environment, prioritizing on the basis of ecosystem services and selecting only those sites of highest values, is potentially problematic from a biodiversity perspective.…”
Section: Ecosystem Services Arguments For Urban Conservationmentioning
confidence: 99%
“…These spatial studies may provide a series of useful tools that can effectively integrate ecosystem services into planned or current conservation programs (Naidoo et al, 2008), assess the effects of implementing ecological policies, and identify priority areas for ecosystem-service management (Egoh et al, 2011). Such information is particularly important to allow for the modification of current ecological conservation planning and policies in a more beneficial and targeted way.…”
Section: Introductionmentioning
confidence: 99%